2017
DOI: 10.3390/md15060174
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supercritical Carbon Dioxide Extraction Parameters on the Biological Activities and Metabolites Present in Extracts from Arthrospira platensis

Abstract: Arthrospira platensis was used to obtain functional extracts through supercritical carbon dioxide extraction (SFE-CO2). Pressure (P), temperature (T), co-solvent (CX), static extraction (SX), dispersant (Di) and dynamic extraction (DX) were evaluated as process parameters through a Plackett–Burman design. The maximum extract yield obtained was 7.48 ± 0.15% w/w. The maximum contents of bioactive metabolites in extracts were 0.69 ± 0.09 µg/g of riboflavin, 5.49 ± 0.10 µg/g of α-tocopherol, 524.46 ± 0.10 µg/g of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 67 publications
(105 reference statements)
1
21
0
Order By: Relevance
“…In regard to the composition of monosaccharides from depleted cyanobacterial biomass, it has been reported that these microorganisms have different types of polysaccharides, peptoglycanes in the wall cell and glycogen granules in the intracellular vesicles (Van Eykelenburg, 1977). During the SFE process, the cell wall of the cyanobacteria is broken due to the high temperature and pressure required for the process (Esquivel-Hernández et al, 2017a). This leads to the release of the different polysaccharides embedded in the cell wall.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In regard to the composition of monosaccharides from depleted cyanobacterial biomass, it has been reported that these microorganisms have different types of polysaccharides, peptoglycanes in the wall cell and glycogen granules in the intracellular vesicles (Van Eykelenburg, 1977). During the SFE process, the cell wall of the cyanobacteria is broken due to the high temperature and pressure required for the process (Esquivel-Hernández et al, 2017a). This leads to the release of the different polysaccharides embedded in the cell wall.…”
Section: Resultsmentioning
confidence: 99%
“…The cyanobacterial strain Arthrospira platensis used throughout this work was cultivated as reported in (Esquivel-Hernández et al, 2017a) (Esquivel-Hernández et al, 2017b.…”
Section: Cyanobacteria Cultivationmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Pressure and temperature have to be chosen appropriately to exceed the supercritical point of CO2 at 304.12 K and 73.7 bar. 14,15 Subsequently, they have to be kept high enough, to preserve the CO2 in supercritical state. For choosing temperature and pressure, it has to be taken into account that increasing percentage of co-solvent increases pressure and temperature required to reach the supercritical point of the mixture.…”
Section: Introductionmentioning
confidence: 99%
“…The literature proposes different lutein extraction technologies from S. almeriensis but the findings are not sufficient to establish a clear methodological and a defined approach for the evaluation of extraction costs, yield, and quality of the final extracts [19,20,21,22,23,24,25,26].…”
Section: Introductionmentioning
confidence: 99%